Unraveling the full impact of SPD_0739: a key effector in S. pneumoniae iron homeostasis - Edroyal Womack; Melina Antone; Zehava Eichenbaum (Microbiology Spectrum)
ABSTRACT Streptococcus pneumoniae is a common member of the nasopharynx commensal microflora and the leading etiological agent of bacterial pneumonia in young children and aging adults. SPD_0739, a highly expressed lipoprotein, is the predicted substrate-binding component of an ABC transporter linked to the uptake of nucleosides and heme by independent studies (named PnrA or Spbhp-37, respectively). Here, we demonstrate that SPD_0739 binds heme in vitro and contributes to the bacterial binding to hemoglobin. A ∆spd_0739 strain exhibited growth attenuation that was relieved by the inactivation of the piuBCDA transporter. Knocking out spd_0739 in the wild type, or the ΔpiuBCDA strain resulted in heme accumulation, higher sensitivity to heme toxicity, and a small growth reduction compared to medium supplemented with a nucleoside mixture. In addition, spd_0739 loss results in higher iron- and heme-related gene expression and lower H2O2 production. Altogether, the data are consistent with a role in nucleoside import and show that SPD_0739 does not import heme. Instead, it indirectly influences iron and heme metabolism, linking nucleosides and iron status in S. pneumoniae.IMPORTANCES. pneumoniae obtains growth essential iron from hemoglobin and other host hemoproteins. Still, the bacterial mechanisms involved are only partially understood, and there are inconsistent reports regarding the function of several transporters implicated in iron uptake. In this study, we clarified the role of PnrA/Spbhp-37, a ligand-binding protein previously linked to nucleoside or heme by different studies. We present data supporting a role in nucleoside scavenging rather than heme import and reveal that PnrA/Spbhp-37 modulates iron and heme uptake, likely by influencing the nucleoside cellular pool. Hence, this work provides a new understanding of a process critical to the pathophysiology of a significant human pathogen. Moreover, PnrA/Spbhp-37 is an abundant and immunogenic surface protein that is highly conserved. Hence, this study also clarifies the function of a promising vaccine target.